Fluorescent bent-core mesogens with thiophene-based central unit. Issue 12 (25th September 2020) - Matraszek, Joanna; Grześkiewicz, Katarzyna; Górecka, Ewa; Pociecha, Damian
ABSTRACT: New bent-core mesogens with thiophene central ring were designed to obtain fluorescent and conductive liquid crystlline phases. Depending on the number of terminal chains and the length of lateral substituent at central unit either calamitic or columnar phases were formed. All the synthesised compounds showed high quantum efficiency of fluorescence in solution, 0.9, that was however reduced to 0.15 in condensed state. The light emitted from nematic or columnar phase was linearly polarised. Quenching of fluorescence in condensed state, together with observed red shift of emission maximum wavelength, evidenced formation of J-aggregates or weak excimers. Aggregation was also monitored by dynamic light scattering in water/tetrahydrofuran (THF) solutions. Graphical abstract: uf0001